Uplift of Kelud Volcano Prior to the November 2007 Eruption as Observed by L-Band Insar - Lubis, Ashar Muda (Journal of Engineering and Technological Sciences, 2014)
Kelud volcano, a stratovolcano with summit elevation of 1731 m above sea level, is considered to be one of the most dangerous volcanoes in Java, Indonesia. Kelud volcano erupts frequently, with the most recent eruption occurred on November 3, 2007. Therefore, volcano monitoring, especially detecting precursory signals prior to an eruption, is important for hazard mitigation for Kelud volcano. Interferometric Synthetic Aperture Radar (InSAR) has been proven to bea powerful tool for investigating earth-surface deformation. Hence, we applied D-InSAR (differential InSAR) in an effort to identify pre-eruptive deformation of Kelud volcano before November 2007 eruption. SAR images, L band ALOS-PALSAR, were used to construct 3 coherent interferograms between January to May 2007. We used the D-InSAR technique to remove topographic effects from interferometry images. During the interval observation, we detected a continuous inflation with a maximum line-of-sight (LOS) displacement of 11cm. Uplift of Kelud volcano was also observed by the tiltmeter 1-2 months prior to the November 2007 eruption. We interpret this inflation as a manifestation of increased volume of magmatic material in the shallow reservoir and magmatic migration towards the surface, indicating an imminent eruption. This study confirms that InSAR technique is a valuable tool for monitoring volcano towards better hazard mitigations.